Persistent acyclic Cp*Ir(III) complexes and their reactivities in cross-coupling reactions - Yimin Wu; Yayin Deng; Guangying Tan; Jingsong You (Nature Communications)
Abstract Iridium(III) complexes play a prominent role in organometallic chemistry, with significant research efforts directed toward Cp*Ir(III) species, broadly categorized into cyclic and acyclic types. Although studies on these two classes began roughly simultaneously, the development of acyclic Cp*Ir(III) complexes has lagged significantly behind their cyclic counterparts. Herein, we report a general and efficient strategy for synthesizing various persistent aryl Cp*Ir(III)(CO)Cl complexes directly from aryl aldehydes, with in situ generated CO as a stabilizing ligand. These acyclic Cp*Ir(III) complexes showcase exceptional reactivity, undergoing reactions with up to eight classes of nucleophiles to generate diverse diorganoiridium(III) species with remarkable stability. Electrochemical analysis of these complexes provides insights into their reductive elimination processes. Guided by these findings, Cp*Ir(III)-mediated decarbonylative C–C and C–O cross-couplings of aryl aldehydes are successfully developed. This study establishes a robust platform for the exploration of acyclic Cp*Ir(III) complexes, paving the way for further advancements in iridium(III) chemistry.